2015
DOI: 10.1002/pat.3553
|View full text |Cite
|
Sign up to set email alerts
|

Behavior of biodegradable composites based on starch reinforced with modified cellulosic fibers

Abstract: The aims of this study were to develop composite films based on potato starch and cellulose modified with toluenediisocyanate, to investigate their morphology and structure, and to evaluate their behavior to enzymatic hydrolysis and their potential use to manufacture of biodegradable seedling pots. The effects of modified cellulosic fibers upon mechanical properties and biodegradability of composite materials based on starch matrix were investigated by tensile strength tests, Fourier infrared spectroscopy, X-r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 29 publications
1
5
0
Order By: Relevance
“…As in the case mixture of birch and aspen cellulose, birch cellulose had a reinforcing effect, confirmed by mechanical properties. Thus, the tensile strength of starch has increased by addition of birch cellulose in the starch matrix from 2.0 ± 0.76 to 2.77 ± 0.59 MPa.…”
Section: Discussionsupporting
confidence: 52%
See 4 more Smart Citations
“…As in the case mixture of birch and aspen cellulose, birch cellulose had a reinforcing effect, confirmed by mechanical properties. Thus, the tensile strength of starch has increased by addition of birch cellulose in the starch matrix from 2.0 ± 0.76 to 2.77 ± 0.59 MPa.…”
Section: Discussionsupporting
confidence: 52%
“…Our study concerned on manufacture of biodegradable seedlings pots (used in greenhouses) which could have the capacity to retain heavy metals, acting like a barrier against soil pollutants. Thus, we found that starch reinforced with TDI‐modified birch cellulose, which have good mechanical properties and is biodegradable (as we stated before), is able to retain, in a proportion of about 60%, lead, zinc, and copper ions.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations